Microneedle Array Patches: Characterization and in -vitro Evaluation - Sadeq, Zainab A. (Iraqi Journal of Pharmaceutical Sciences, 2021)
Patch in transdermal drug delivery(TDDS) used to overcome the hypodermic drawback, but these patch also have absorption limitation for hydrophilic and macromolecule like peptide and DNA. So that micronized projection have the ability for skin penetration developed named as microneedle. Microneedle drug delivery system is a novel drug delivery to overcome the limitation of TDDS like skin barrier restriction for large molecule. Microneedle patch can penetrate through skin subcutaneous into epidermis, avoiding nerve fiber and blood vessel contact. There are many type of microneedle patch like solid, polymer, hallow, hydrogel forming microneedle and dissolving microneedle with different method of microfabrication